The Right to Equal Access to Health in International Law - Phi Hoang, Mai (VNU Journal of Science: Legal Studies, 2025)
In a world striving for progress, equity, and equality, health disparities continue to persist, both in access to health-care services and health outcomes. These disparities may result in violations of fundamental human rights, including the right to life, the right to human dignity, the right to equality, and the right to freedom from discrimination. The international legal framework on health plays an important role in addressing global health-related inequalities. This article examines the right to equal access to health in international law and evaluates the difficulties and challenges that the current legal framework faces in ensuring the effective protection of this right.